Knowledge-utilization gap regarding modern methods of contraception among rural women attending an outreach health centre in North Delhi - Behera, Shyambhavee; Yadav, Kartikey (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Even with nearly five decades of launch of the programme, only half of the eligible couples in the country are using any modern method of contraception and 12% still have an unmet need for family planning, as per National Family Health Survey 4 (NFHS 4). The current study aims to estimate the knowledge and use of the contraceptive practices and its socio-demographic determinants among women (15-49 years) attending Health Centre in a rural village of North Delhi. Methods: A cross sectional study was conducted in July, 2018 at outreach Rural Health Training Centre (RHTC) in North Delhi. Hundred currently married women in the reproductive age group (15-45 years) coming to outreach centre participated in the study. The study participants were interviewed using pretested, semi structured questionnaire. Results: Although 96% of the study participants had knowledge regarding any of the modern method of contraception, only 57% were using them (including condom, OCP, IUCD and sterilization). Reasons for not using any kind of contraceptive included poor reliability, lack of proper knowledge regarding availability and use, partner opposition and willingness to have a child. Conclusions: Although knowledge about contraceptives was good, the utilization was very low. Even in presence of established and ever-expanding services available, the current study reported a remarkable gap in the individual contraceptive knowledge and utilization. Thus, providing correct knowledge to the couple as a single unit and its reiteration at regular interval becomes the pivot in filling this knowledge-utilization gap.